2018
DOI: 10.5539/ijef.v10n11p110
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Credit Risk Management Practices of Adansi Rural Bank Limited

Abstract: Rural banks in Ghana are not exempted from the risk exposures associated with managing credit. Given their importance to the economy, appropriate measures should be taken to mitigate credit risk exposures of rural banks in the country. The study critically examines the credit risk management practices of rural banks in Ghana making reference to Adansi Rural Bank Limited. The study was carried out to examine the credit management practices, credit policies and strategies for managing credit as well as challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The speed of the lending process refers to the extent to which a financial institution or lender can complete the procedures and requirements needed to provide credit to a prospective borrower (Odonkor, 2018). The lending process includes assessing the eligibility of the borrower, determining the loan amount, setting interest rates, as well as all other administrative stages needed before the credit is approved and funds are distributed to the borrower (Lailiyah, 2014).…”
Section: Speed Of the Editing Processmentioning
confidence: 99%
“…The speed of the lending process refers to the extent to which a financial institution or lender can complete the procedures and requirements needed to provide credit to a prospective borrower (Odonkor, 2018). The lending process includes assessing the eligibility of the borrower, determining the loan amount, setting interest rates, as well as all other administrative stages needed before the credit is approved and funds are distributed to the borrower (Lailiyah, 2014).…”
Section: Speed Of the Editing Processmentioning
confidence: 99%
“…Studies have shown that a bank's business success and even survival depend to a large extent on the ability of the bank management to construct and implement sound policies on credit risk. Many delinquency problems could have been avoided if the management can ensure that the earlier lending processes are conducted correctly of which failure to comply will lead to lower credit scores and high likelihood of non-payment [27][28]. Thus, reviewing the key variables that should be included in the credit scoring model will lead to a better screening process with the hope to see improvement on asset quality in terms of impaired asset position, better management of credit risk, improvement of turnaround time for new application, and cost saving [16], which in all will cumulatively contribute to the development of bank efficiency and profitability.…”
Section: Introductionmentioning
confidence: 99%